CARACTERIZAÇÃO DE METABÓLITOS E ATIVIDADE CITOTÓXICA DO EXTRATO DE Penicillium purpurogenum DE AMBIENTE MARINHO EM MODELO DE CÂNCER DE MAMA IN VITRO E IN VIVO. - TELES, Amanda Mara (2020)
Microfungi are a promising yet unexplored source of new chemical substances with antitumor activity, which in this scenario represent an area with potential for development. To further elucidate the role of Penicillium purpurogenum extract, this study investigated the in vitro antitumor effect on breast tumor cells (MDA-MB-231 and MCF-7) and an in vivo murine Ehrlich tumor model. P. purpurogenum was fermented for 21 days, filtered, concentrated and lyophilized, giving rise to two extracts: ethyl acetate extract of the broth (FR1) and of the mycelial biomass (FR2). For the determination of the chemical composition of the extracts a chemical analysis was performed by direct infusion (ESI/MS). For the evaluation of the cytotoxicity, a MTT [(3-fluorouracil-2-yl) -2,5-diphenyl-tetrazolium bromide] assay was performed with cancer cell lines in the times of 24, 48 and 72 hours. In the in vivo experiment with Ehrlich's tumor, Swiss females were separated into seven groups (n = 10 / group). The intraperitoneal treatment was done daily with phosphate buffer solution in the negative control group (CTL-), with cyclophosphamide (25 mg/kg) in the positive control group (CTL+) and the fungus extract (FR1) at doses 4, 20 and 100 mg/kg in the experimental group. Half of the animals in each group were euthanized 15 days after tumor inoculation, and the other half was kept alive for survival follow-up. Tumor development was evaluated by the weight of the animals, volume and area of the inoculated paw and, after euthanasia, the tumor was weighted. Total blood was collected for the determination of haematological parameters. Spleen, medulla and draining lymph node were obtained for lymphoid cell count. Fragments of the paw with tumor, kidney and liver were histopathologically evaluated. The results of the chemical analysis demonstrated that extracts FR1 and FR2 are rich in meroterpenoids. In the in vitro evaluation, the FR1 extract presented cytotoxicity for MCF-7 with IC50 values of 43.97μg / mL, 23.01μg / mL and 13.85μg / mL. For MDA-MB-23, IC50 values found were of 170 μg / mL, 44.60 μg / mL and 25.46 μg / mL in 24, 48 and 72 h, respectively. All these values were lower when compared to FR2. In the verification of the sensitivity index (SI) it was observed that both extracts showed a better selectivity than the standard drugs. In the in vivo assay, tumor development after treatment demonstrated that the FR1, at all doses, and CTL + treated groups showed a significant reduction of tumor area when compared to CTL-. Treatment with FR1 also promoted an increase in the life expectancy of the tumor bearing animals. The cellularity of the lymphoid organs of FR1 treated animals presented a dose dependent reduction when compared to CTL-. When evaluating the cytokines in the serum of the animals, TNF-α production was higher in the non-induction group treated with the extract when compared to CTL-. There was no change in the haematological parameters analyzed in any of the groups. Regarding the histopathological analysis, the groups treated with the extract at doses of 20 and 100 mg/kg presented less intense inflammatory infiltrates. The groups treated with higher concentrations of the extract showed smaller areas of necrosis. These results indicate that the extract of P. purpurogenum exhibits antitumor property, suggesting that its immunomodulatory role would be involved in this response.